626. Tackling the HIV Epidemic in South Florida: Patient Insights on Approaches for HIV Counseling, Testing, and Access to Prevention or Treatment. (31st December 2020) - Fallon, Stephen J; Molnar, Kimberly; Taneva, Ekaterina S; Simone, Laura; Carter, Jeffrey; Sapir, Tamar
Abstract: Background: The South Florida Metropolitan Statistical Area has for several years recorded the highest HIV incidence in the nation, and prevalence in the top three of all counties. To address the alarming disparity in HIV impact, we developed a survey study to learn about the beliefs, attitudes, and perspectives of persons who accessed services at an HIV community-based organization in South Florida. Methods: Surveys were administered in English and Spanish to 109 persons who visited a community-based HIV service provider (Latinos Salud) at any of its three South Florida sites in April 2019. The survey evaluated the participants' perspectives on different avenues for HIV counseling, screening, and accessing HIV medications for prevention or treatment. Results: The majority of survey participants were male (90%), homosexual/gay/queer (75%), and Hispanic/Latino (56%; Table 1). Participants' self-reported their HIV status as negative (64%), positive (30%), or unknown (6%; Table 1). Of those not currently living with HIV, 77% reported having been tested within the past 6 months, and 81% reported recent engagement in high-risk activities (Table 1). Most participants considered using social media to promote awareness of HIV and related services a good idea (Table 2). Large proportions of participants endorsed receiving HIV counseling through in-person conversations with clinicians (91%), staff at community-based organizations (83%), friends (83%), telehealth visits (69%), conversations with teachers (63%), or church members (56%; Table 2). Most participants endorsed a range of both clinical (e.g. local health clinic) and non-clinical (e.g. mobile van) locations as acceptable settings for HIV testing (Table 2). Large proportions of participants endorsed receiving medications to prevent or treat HIV immediately after testing (82%), by home delivery (78%), or through telehealth (60%; Table 2). Meaningful associations were found between certain patient demographics (race/ethnicity, testing history, or insurance status) and the participants' perspectives on specific strategies (Table 3). Table 1. Participant Characteristics Table 2. Participants' Views on Strategies for HIV Counseling, Testing, and Access to Medications Table 3. Participants' Views on Strategies for HIV Counseling, Testing, and Access to Medications Stratified by Patient Characteristics Conclusion: These real-world findings can be used to inform clinic- and community-based interventions tailored to individual patient characteristics. Disclosures: Tamar Sapir, PhD, Gilead Sciences, Inc. (Other Financial or Material Support, Independent medical education grant)